2019
DOI: 10.7759/cureus.5277
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography-based Analysis of Tibial Tuberosity–Trochlear Groove Distance in Indian Population

Abstract: AimTo study the tibial tuberosity-trochlear groove distance (TT-TG) in normal Indian population and the variation of the same in relation to tibial size using computed tomography (CT) of knee.MethodsCT of 100 knees (62 males and 38 females) were assessed. TT-TG distance and maximal medio-lateral (MML) distance of tibia was measured on axial CT scans. The modified TT-TG (mTT-TG) was calculated as the ratio of TT-TG and MML.ResultsThe average TT-TG distance was 13.01 (±2.84) mm for the entire group with males an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Similar to our result, a CT‐based analysis of TT‐TG distance in the Indian population showed a mean TT‐TG distance with no significant differences between different sexes . 22 Thus, our findings provide new insights into TT‐TG measurements, which at any point under the femur pulley ditch can be used as a parameter to evaluate patellofemoral stability. A reference range for the TT‐TG distance of young and middle‐aged population was provided, and the TT‐TG threshold value should be reduced when assessing patellofemoral stability among the Chinese population.…”
Section: Discussionmentioning
confidence: 71%
“…Similar to our result, a CT‐based analysis of TT‐TG distance in the Indian population showed a mean TT‐TG distance with no significant differences between different sexes . 22 Thus, our findings provide new insights into TT‐TG measurements, which at any point under the femur pulley ditch can be used as a parameter to evaluate patellofemoral stability. A reference range for the TT‐TG distance of young and middle‐aged population was provided, and the TT‐TG threshold value should be reduced when assessing patellofemoral stability among the Chinese population.…”
Section: Discussionmentioning
confidence: 71%
“…Various studies have evaluated the normal mean TT-TG distance in different ethnicities. 1,2,[5][6][7][8] However, there are limited studies in Southern Chinese population. It is crucial to determine the reference value for Southern Chinese population in order to apply TT-TG distance in clinical practice appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…1 There are many studies which had shown different reference values for different ethnicities. 1,2,[5][6][7][8] The first aim of this study is to determine the reference TT-TG distance on Magnetic Resonance Imaging (MRI) in Southern Chinese population. The second aim is to investigate the correlation between TT-TG distance and (i) age, (ii) sex, (iii) height, (iv) weight and (v) Body Mass Index (BMI) respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, small sample sizes and diverse radiographic methods without standardization of patient positioning or the knee-flexion angle have precluded a consensus on the exact cutoff value 12,16 . Furthermore, insufficient data have been reported for the Chinese Han population, and variation between different populations has been detected and is not considered negligible [17][18][19] . The TT-TG distance is also affected by its components (i.e., tibial tubercle lateralization, trochlear groove medialization, and tibiofemoral rotation) 20 and femoral trochlear dysplasia 21,22 .…”
mentioning
confidence: 99%